Diagnostic assessment of haemorrhagic rash and fever. Issue 2 (1st August 2001) - Nielsen, H E; Andersen, E A; Andersen, J; Böttiger, B; Christiansen, K M; Daugbjerg, P; Larsen, S O; Lind, I; Nir, M; Olofsson, K
Abstract : AIMS: To establish criteria for early distinction between meningococcal disease and other conditions with similar clinical features, and to identify other causes for haemorrhagic rashes accompanied by fever. METHODS: In a prospective study, 264 infants and children hospitalised with fever and skin haemorrhages were studied. RESULTS: We identified an aetiological agent in 28%: 15% had meningococcal disease, 2% another invasive bacterial infection, 7% enterovirus infection, and 4% adenovirus infection. Five clinical variables distinguished between meningococcal disease and other conditions on admission: (1) skin haemorrhages of characteristic appearance; (2) universal distribution of skin haemorrhages; (3) maximum diameter of one or more skin haemorrhages greater than 2 mm; (4) poor general condition (using a standardised observation scheme); and (5) nuchal rigidity. If any two or more of these clinical variables were present, the probability of identifying a patient with meningococcal disease was 97% and the false positive rate was only 12%. This diagnostic algorithm did not identify children in whom septicaemia was caused by other bacterial species.